Reversible Shaping of Microwells by Polarized Light Irradiation. (3rd December 2017) - Pirani, Federica; Angelini, Angelo; Frascella, Francesca; Descrovi, Emiliano
Abstract : In the last years, stimuli-responsive polymeric materials have attracted great interest, due to their low cost and ease of structuration over large areas combined with the possibility to actively manipulate their properties. In this work, we propose a polymeric pattern of soft-imprinted microwells containing azobenzene molecules. The shape of individual elements of the pattern can be controlled after fabrication by irradiation with properly polarized light. By taking advantage of the light responsivity of the azobenzene compound, we demonstrate the possibility to reversibly modulate a contraction-expansion of wells from an initial round shape to very narrow slits. We also show that the initial shape of the microconcavities can be restored by flipping the polarization by 90°. The possibility to reversibly control the final shape of individual elements of structured surfaces offers the opportunity to engineer surface properties dynamically, thus opening new perspectives for several applications.